2016
DOI: 10.1038/srep32884
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic differentiation of preosteoblasts on a hemostatic gelatin sponge

Abstract: Bone tissue engineering provides many advantages for repairing skeletal defects. Although many different kinds of biomaterials have been used for bone tissue engineering, safety issues must be considered when using them in a clinical setting. In this study, we examined the effects of using a common clinical item, a hemostatic gelatin sponge, as a scaffold for bone tissue engineering. The use of such a clinically acceptable item may hasten the translational lag from laboratory to clinical studies. We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
50
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 54 publications
2
50
0
3
Order By: Relevance
“…We note that the measured thickness is slightly larger than the expected value probably because of a thin water layer or a difference in the interaction force of tip with the substrate and MnPS3 flake as discussed in Ref. [11]. A similar observation has been often made in other mechanically exfoliated vdW materials like graphene, 1,20 TMDCs, [21][22][23] and NiPS3.…”
supporting
confidence: 81%
See 3 more Smart Citations
“…We note that the measured thickness is slightly larger than the expected value probably because of a thin water layer or a difference in the interaction force of tip with the substrate and MnPS3 flake as discussed in Ref. [11]. A similar observation has been often made in other mechanically exfoliated vdW materials like graphene, 1,20 TMDCs, [21][22][23] and NiPS3.…”
supporting
confidence: 81%
“…A similar observation has been often made in other mechanically exfoliated vdW materials like graphene, 1,20 TMDCs, [21][22][23] and NiPS3. 11,13 It is rather common to observe carrier transport in a metal/insulator/metal junction being affected by a band alignment in accordance with the Schottky-Mott theory. 24 Figure 1 Therefore, we can determine the barrier height ΦB from a difference between an electron affinity s of MnPS3 and a work function of Pt-Ir (5.4 eV).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…The hemostatic gelatin sponge, Spongostan TM , is prepared from purified type A pork skin, and its biosafety in clinical applications, especially to control bleeding during surgery, has long been proved [56, 57]. In vivo studies have shown good biocompatibility of Spongostan TM without any immune response during bone formation [36]. The main reasons that we chose this scaffold are its biocompatibility and biodegradation with MSCs and absence of autofluorescence [36].…”
Section: Discussionmentioning
confidence: 99%